Resourcing the sustainability and recovery of the sport sector during the Coronavirus pandemic - Kokolakakis, T.; Edmondson, L.; Kung, S. P.; Storey, R. (Commonwealth Moves, 2020)
This paper addresses the impacts of COVID-19 on the sport economies of Commonwealth member countries. The main policy ideas that emerge suggest that: • Sport is very effective at increasing employment. Investment in sport can be used as a policy tool during recession (such as in the current crisis) to reverse the effects of economic decline. • Additionally, research has demonstrated that that every £1 spent on sport generates £1.91 in health and social benefits. • Many of the social benefits of sport relate to young people. This is especially important in many Commonwealth countries, where young people make up a large percentage of the population. • According to existing economic assessments, the importance of sport in the national economies usually varies between 1 per cent and 2.3 per cent in terms of gross value added and employment. • Sport is strongly associated with sectors such as tourism and accommodation, which the lockdown period hit hard. At the same time, sport organisations have to maintain their basic infrastructure, which has led to a decline in their surpluses. • Strict lockdown measures were implemented in almost all Commonwealth countries, entailing an effective closure of the sport and tourism sectors. In fact, the effect of the lockdown on sport will be many times more severe than the effect on the overall economy. • The human cost in developing countries will be increasingly high, given their dependence on informal labour and the limited capacities of the various health systems. According to the World Bank, informal employment in developing countries can be as high as 60 per cent of total employment. • Diversified investment, innovative financial options and new partnerships are required to help stimulate the domestic sport market and industry.